Composição corporal de matrizes de corte submetidas a diferentes horários de arraçoamento - Toledo, Taiani dos Santos de (2015)
The different feeding schedules used in the poultry industry contribute to improve the nutrients distribution in the animal, as well as egg production. The study was carried out to analize the corporal composition of broiler breeders fed in different feeding schedules and their effect in body weight and body weight gain, as well as egg production. The broiler breeders were fed in three feeding schedules. The feeding schedules evaluated were: 1- a single feeding at 08:00 am, 2- twice daily feeding (50% at 08:00 am and 50% at 3:00 pm), 3- a single feeding at 3:00 pm. The hens were allocated in a completely randomized design of 3 treatments with 5 replications of 22 females and 3 males per repetition, to evaluate the corporal composition parameters were slaughtered two hens per repetition. Body weight, body weight gain, egg production, dry matter, mineral matter, crude protein, ether extract, calcium and phosphorus levels were evaluated. The feeding schedule late had higher body weight (P=0.0273) and body weight gain (P=0.0981) than early feeding schedule used. The first feeding schedule showed better egg production (P=0.0300) than the third feeding schedule. The percentage of ash (P=0.0741) and phosphorus (P=0.0875) were higher in broilers breeders fed at 8 am than hens fed at 3 pm, not different from the treatment 2. The calcium content were not affected by feeding scheduler used. The broiler breeder feeding at 8:00 am had more level of dry matter, crude protein and lower ether extract than feeding schedule late. Broiler breeder fed with feeding schedule late had lower egg production and higher body weight gain than others, consequently the most body fat deposition.